Current mode proportional resonant controlled multi input–SEPIC-re-boost-system - B. Jagadish Kumar; Basavaraja Banakara (Institute of Advanced Engineering and Science, 2019)
The intention of this paper is to identify a suitable controller for closed loop multi converter system for multiple input sources and to improve time response of high-gain-step up-converter. Closed-loop Multi Converter System (MCS) is utilized to regulate load-voltage. This effort recommends suitable-controller for closed-two loop-controlled-SEPIC-REBOOST Converter fed DC motor. The estimation of the yield in open-two loop and closed- two-loop-circuit has been done using MATLAB or Simulink. Closed-two loop-control of Multi Converter System with Propotional+Integral (PI)- Propotional+Integral (PI) and Proportional+Resonant (PR) - Proportional+Resonant (PR) Controllers are investigated and their responses are evaluated in conditions of rise time, peak time, settling time and steady state error. It is seen that current-mode PR-PR controlled MCS gives better time domain response in terms of motor speed. A Prototype of MCS has been fabricated in the laboratory and the experimental-results are authenticated with the simulation-results.